Molecular Characterization of Some Popular Fish Species in Saudi Arabia - Sabry, Ayman M.; Hassan, Mohamed M.; Mohamed, Alaa A. (International Journal of Applied Sciences and Biotechnology, 2015)
The present work aims to molecularly characterize some popular Saudi fish species. Seven popular Saudi fish species namely, Morgan (Nemipteru sjaponicus), Mousa (Solea solea), Hamor (Greasy grouper), Shour (Lethrinus lentjan), Dennis (Caranxsex fasciatus), Harid (Scarus arabicus) and Black surgeon (Acanthurus gahhm) were characterized using six RAPD and three ISSR as well as Rep-PCR markers. These markers produced 187 distinct bands 89.4% were considered as polymorphic bands and 10.6% were considered as monomorphic bands. The RAPD OPA-06 primer revealed 100% polymorphism for 19 produced bands where band width ranged from 190 to 2100 bp. Likewise Rep- PCR ERIC1R primer exhibited 100% polymorphism for 18 bands produced bands where band width ranged from 50 to 1400bp. Data of the three types of genetic markers were combined for phylogenetic analysis. The resulted dendergram produced two large linages with around 59% genetic similarity. One linage only included Morgan (Nemipteru sjaponicus), and the other linage comprised the other six species. This result suggested that this six species were descended from Morgan fish. The second linage comprised two clades; the first clade contained four species (Mousa, Hamor, Shour, and Dennis), where the next clade included only Harid and Black surgeon. Generally genetic distance among native fishes was relatively low. The smallest genetic distance (0.512) was estimated between Shour fish and Black surgeon fish. To the best of our knowledge this work is breaking new ground in two directions, first, molecular characterization of Saudi fish, second employment Rep- PCR genetic marker for molecular characterization of fish species. This work could be considered as preliminary work towards an establishment of Saudi genetic conservation program. Int J Appl Sci Biotechnol, Vol 3(2): 359-366 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12747